A breath ammonia analyser for monitoring patients with end-stage renal disease on haemodialysis. Issue 1 (2nd January 2017) - Limeres, J.; Garcez, J. F.; Marinho, J. S.; Loureiro, A.; Diniz, M.; Diz, P.
Abstract: Objective: Breath ammonia measurement has attracted increasing interest for clinical diagnosis and metabolic status monitoring. This pilot study aims to evaluate a simple detection method to measure breath ammonia levels in haemodialysis patients. Materials and methods: The study group comprised 44 adults undergoing haemodialysis and a control group of 44 age- and sex-matched individuals with a glomerular filtration rate >90 mL/min. To measure breath ammonia concentration, we designed a device based on that used to monitor atmospheric air, which uses a specific colorimetric tube. A single operator took two readings from each haemodialysis patient (one predialysis and one postdialysis) and one reading from each control. The results were compared with the urea concentrations in blood and saliva. Results: Breath ammonia concentration correlated significantly with blood urea both predialysis ( P  < 0.001; R 2  = 0.55) and postdialysis ( P  = 0.009; R 2  = 0.25), as well as with predialysis saliva urea concentration ( P  < 0.001; R 2  = 0.24). Ammonia was not detectable in breath of any of the control group. Conclusions: The collection of breath samples in polyvinyl fluoride bags and their subsequent analysis using colorimetric tubes is a simple, noninvasive method that enables variations in breath ammonia concentration to be measured rapidly in haemodialysis patients. Using this method, we found that the breath ammonia concentration correlated significantly with the blood urea concentration before and after haemodialysis.